Government regulations and their impact on land division and compensation - D. S. S. Wijayanti; I. Koeswahyono; L. D. Andreassari (Law and Safety)
Land tenure inequality in Indonesia remains a fundamental challenge to achieving social justice, as mandated by the 1945 Constitution. Government Regulation No. 224/1961 on the Implementation of Land Division and Compensation serves as a critical legal framework to advance agrarian reform through land redistribution to underprivileged communities. This study evaluates the effectiveness of this regulation by examining its implementation in Srimulyo Village, Dampit District, Malang Regency, using a socio-legal approach. The analysis integrates normative and empirical perspectives to explore policy performance. The implementation of land redistribution faces significant challenges, including discrepancies in inventory data, weak inter-agency coordination, and low community participation. Ownership conflicts due to inaccurate data and weak documentation systems also exacerbate the situation on the ground. The study has found that land redistribution does not often reach the target groups most in need, and the lack of adequate monitoring mechanisms has led to suboptimal implementation of the program. The findings show that despite the progress made in legalising land rights, there are still significant challenges. These include discrepancies in land inventory data, inadequate coordination among implementing agencies, and limited community engagement. The study concludes that strengthening inter-agency coordination, digitizing land information systems, and enhancing accessibility through capital, training, and infrastructure support are essential to improving policy outcomes. Strategic recommendations are provided to ensure the sustainability of agrarian reform and enhance the welfare of beneficiary communities. With an integrated approach that focuses on community empowerment, land redistribution can be an effective instrument in reducing land tenure inequality and supporting the achievement of social justice sustainably. This research contributes to identifying actionable solutions for addressing the persistent issues in land redistribution efforts in Indonesia.